2001
DOI: 10.1080/00207140108410061
|View full text |Cite
|
Sign up to set email alerts
|

Anterior brain functions and hypnosis: A test of the frontal hypothesis

Abstract: Neuropsychological frontal lobe tests were used to compare individuals with high (n = 8) and low (n = 9) hypnotizability during both baseline and hypnosis conditions. Subjects were assessed on two hypnotic susceptibility scales and a test battery that included the Stroop test, word fluency to letter- and semantic-designated categories, tests of simple reaction time and choice reaction time, a vigilance task, and a questionnaire of 40 self-descriptive statements of focused attention. Effects for hypnotic suscep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
45
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 76 publications
(51 citation statements)
references
References 18 publications
4
45
2
Order By: Relevance
“…Similar e↵ects have been reported for letter fluency (Gruzelier & Warren, 1993;Kallio, Revonsuo, Hamalainen, Markela, & Gruzelier, 2001). These results are clearly in line with the predictions of dissociated control theory (Jamieson & Woody, 2007;Woody & Bowers, 1994).…”
Section: Introductionsupporting
confidence: 80%
“…Similar e↵ects have been reported for letter fluency (Gruzelier & Warren, 1993;Kallio, Revonsuo, Hamalainen, Markela, & Gruzelier, 2001). These results are clearly in line with the predictions of dissociated control theory (Jamieson & Woody, 2007;Woody & Bowers, 1994).…”
Section: Introductionsupporting
confidence: 80%
“…However, Farvolden and Woody (2004) observed no significant baseline performance differences between groups in a word fluency task in a study with a large sample size (30 highs vs. 30 lows). Similarly, non-significant differences on word fluency tasks were reported by Kallio et al (2001) and Aikins and Rey (2001), albeit in studies with small sample sizes.…”
Section: Frontal Executive Functions and Hypnotic Suggestibilitymentioning
confidence: 93%
“…Notably however, just as many studies have observed worse baseline performance by highs (Dixon & Laurence, 1992;Dixon, Brunet, & Laurence, 1990;Farvolden & Woody, 2004;Terhune, Cardeña, & Lindgren, 2011a;Varga, Németh, & Szekely, 2011) or no significant baseline performance differences between high and low suggestible individuals (Aikins & Ray, 2001;Braffman & Kirsch, 2001;Dienes et al, 2009;Jamieson & Sheehan, 2002; Frontal Executive Functions in Hypnosis and Hypnotic Suggestibility 17 Sheehan, 2004;Iani, Ricci, Baroni, & Rubichi, 2009;Kallio et al, 2001;Raz et al, 2002;Varga et al, 2011). For example, in one study with a very large sample size, (n=180) Dienes et al (2009) tested the relationship between hypnotic suggestibility and inhibition using three inhibition tasks.…”
Section: Frontal Executive Functions and Hypnotic Suggestibilitymentioning
confidence: 99%
“…The process of hypnotic induction, regardless of how it is implemented, serves to narrow a personÕs attention. It has been suggested that the effects of hypnosis are due to frontal inhibition (for recent reviews see, Gruzelier, 2000; Kallio, Revonsuo, H€ a am€ a al€ a ainen, Markela, & Gruzelier, 2001). The transient hypofrontality hypothesis suggests further that, similar to meditation, the focused attention of the hypnotic state is the mechanism by which the activation of various prefrontal circuits is decreased, eliminating their computation from figuring into immediate conscious experience.…”
Section: Hypnosismentioning
confidence: 99%
“…Direct evidence for this notion has come from testing hypnotized subjects using various neuropsychological measures such as the Stroop test that depend on prefrontal activation. Results from these studies showed that subjects perform poorly under hypnosis as compared to baseline (Dixon & Laurence, 1992;Nordby, Hugdahl, Jasiukaitis, & Spiegel, 1999;Kaiser, Barker, Haenschel, Baldeweg, & Gruzelier, 1997;Kallio et al, 2001;Sheehan, Donovan, & MacLeod, 1988). In addition, studies measuring event-related potentials during hypnosis also indicate decreased prefrontal activation (Nordby et al, 1999;Kaiser et al, 1997).…”
Section: Hypnosismentioning
confidence: 99%